1990
DOI: 10.1126/science.2218501
|View full text |Cite
|
Sign up to set email alerts
|

Different Tumor-Derived p53 Mutants Exhibit Distinct Biological Activities

Abstract: In its wild-type form, the protein p53 can interfere with neoplastic processes. Tumor-derived cells often express mutant p53. Full-length mutant forms of p53 isolated so far from transformed mouse cells exhibit three common properties in vitro: loss of transformation-suppressing activity, gain of pronounced transforming potential, and ability to bind the heat shock protein cognate hsc70. A tumor-derived mouse p53 variant is now described, whose site of mutation corresponds to a hot spot for p53 in human tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(108 citation statements)
references
References 25 publications
10
97
0
1
Order By: Relevance
“…In terms of the effect of p53 or H-ras individually on tumorigenesis, our findings are consistent with some of the previously published studies (3,18,32). For example, our finding on the effect of p53 is consistent with the results from Halevy et al (18) in which the mutant p53 gene was found to act synergistically with the mutant ras gene to cause malignant transformation of primary rat embryo cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In terms of the effect of p53 or H-ras individually on tumorigenesis, our findings are consistent with some of the previously published studies (3,18,32). For example, our finding on the effect of p53 is consistent with the results from Halevy et al (18) in which the mutant p53 gene was found to act synergistically with the mutant ras gene to cause malignant transformation of primary rat embryo cells.…”
Section: Discussionsupporting
confidence: 83%
“…We hypothesized that the compound transgenic mice carrying activated H-ras and dominant-negative p53 could greatly accelerate mouse skin tumorigenesis because the mutant p53 acts synergistically with mutant ras to cause malignant transformation of primary rat embryo cells (18). In addition, the altered gene expression associated with H-ras and p53 genes was evaluated in normal skin and skin SCC following carcinogen exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these findings strongly indicate that mutant p53 proteins do not represent the mere loss of wt-p53 activities, but gain new additional oncogenic functions which contribute to the development, maintenance, spreading and resistance to anti-cancer treatment of a tumor. Given that some mutant p53 proteins exert a gain of function, the focus of intense research in the p53 field is the elucidation of the molecular mechanisms underlying this activity (Haley et al, 1990;Dittmer et al, 1993;Lin et al, 1995;Vousden and Lu, 2002;Monti et al, 2005). To date, mutant p53 proteins might work through the following molecular scenarios: (a) mutant p53 interacts, sequesters and inactivates proteins whose activities are closely connected to anti-tumoral effects ranging from growth arrest to apoptosis induced by anti-cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal findings by Finlay et al (1988) that point mutations in the wild-type TP53 gene activate the gene for cooperation with an activated ras gene in cellular transformation, research on the hypothesis that mutant p53 is not just an inactivated tumour suppressor, but displays oncogenic activities on its own, has developed into an important section of p53 biology. The term 'gain of function' coined for summarizing the then unknown oncogenic activities of mutant p53 first appeared in a Science article by Halevy et al (1990) and gained further acceptance after the publication of a Nature Genetics paper in 1993 by Dittmer et al (1993), where the term 'gain of function' appeared in the title. By now, a steadily increasing number of laboratories worldwide pursue the idea of a mutant p53 gain of function (GOF).…”
mentioning
confidence: 99%